1. Reflection and rotation matrices

Let $R(\theta)=\left[\begin{array}{cc} \cos(\theta) & -\sin(\theta) \\ \sin(\theta) & \cos(\theta) \end{array}\right]$ denote the 2x2 rotation matrix.

Show that $R(\theta)R(\phi)=R(\theta+\phi)$

Without further matrix calculation, explain why $R(\phi)R(\theta)=R(\theta)R(\phi)$

Anyone willing to help explain how to work this out?

2. Originally Posted by Konidias
Let $R(\theta)=\left[\begin{array}{cc} \cos(\theta) & -\sin(\theta) \\ \sin(\theta) & \cos(\theta) \end{array}\right]$ denote the 2x2 rotation matrix.
Show that $R(\theta)R(\phi)=R(\theta+\phi)$
Without further matrix calculation, explain why $R(\phi)R(\theta)=R(\theta)R(\phi)$
Do you know how to multiply two 2x2 matrices?
Do you know the sine and cosine of the sum of two numbers?
That is all this problem is about.

3. Originally Posted by Konidias
Let $R(\theta)=\left[\begin{array}{cc} \cos(\theta) & -\sin(\theta) \\ \sin(\theta) & \cos(\theta) \end{array}\right]$ denote the 2x2 rotation matrix.

Show that $R(\theta)R(\phi)=R(\theta+\phi)$

Without further matrix calculation, explain why $R(\phi)R(\theta)=R(\theta)R(\phi)$

Anyone willing to help explain how to work this out?

The last part just requires that you observe that addition is comulative and so what you have already proven shows that:

$R(\theta)R(\phi) = R(\theta+\phi) = R(\phi+\theta)=R(\phi)R(\theta)$

CB

4. Originally Posted by CaptainBlack
The last part just requires that you observe that addition is comulative and so what you have already proven shows that:

$R(\theta)R(\phi) = R(\theta+\phi) = R(\phi+\theta)=R(\phi)R(\theta)$

CB
"commutative" not "comulative"!

5. I forgot to ask: Show that $R(\theta)R(\phi)=R(\theta+\phi)$ and give a geometrical interpretation of what this means.

I understand the first bit now but how would you give a geometrical interpretation of the result?